THE EFFECT OF ECONOMIC GROWTH, POPULATION GROWTH AND UNEMPLOYMENT ON POVERTY LEVELS IN INDONESIA - Yuli Annisa; Ratna; Fanny Nailufar; Noviami Trisniarti (LPPM Universitas Malikussaleh, 2026)
This study aims to analyze the effect of economic growth, population growth, and unemployment on poverty levels in Indonesia in both the short and long run. The data used are time series data for the period 1991–2024, sourced from the Central Bureau of Statistics and the World Bank. The analytical method employed is the Auto Regressive Distributed Lag (ARDL) model to examine both short-term and long-term relationships among variables. The results show that in the short run, economic growth has a negative effect on poverty levels in Indonesia, while population growth and unemployment have positive effects on poverty levels. In the long run, economic growth also has a negative effect on poverty levels, whereas population growth and unemployment continue to have positive effects on poverty levels. This implies that an increase in economic growth can reduce poverty levels. Conversely, population growth and unemployment contribute to an increase in poverty levels.